Diversity of toxin genotypes and antimicrobial susceptibility of Clostridium perfringens isolates from feces of infants - AL Radaideh, Alaa J; Badran, Eman F; Shehabi, Asem A (Germs (Bucureşti), 2019)
This study investigated the most important epidemiological characteristics of strains colonizing the intestine of Jordanian infants. A total of 302 fecal samples were collected from Jordanian infants aged ≤ 1 year from patients hospitalized in the neonatal intensive care unit and from the outpatient department. Samples were cultured for detection of and evaluation of their antimicrobial resistance; identification of their potential toxins genes was performed using PCR. Overall the colonization rate was 27.2% (82/302). Infants aged ≤ 6 months showed significantly higher (p<0.004) colonization than older infants. The occurrence rates of isolates carrying potential specific toxin genes were as follows: alpha toxin 95.1% (78/82), beta-2 toxin 69.5% (57/82), beta toxin 14.6% (12/82), and only 2.4% (2/82) epsilon toxin. No isolate carried the iota toxin. Genotype A was the most prevalent among isolates (78.1%). The antimicrobial resistance rates of isolates were 20% to metronidazole and erythromycin, 16.7% to levofloxacin, and 6.7% to vancomycin. This study demonstrates that the majority of isolates from feces of Jordanian infants were classified as type A, few isolates were classified as type C and type D, and all were negative for potential enterotoxin genes causing diarrhea.